Nitric oxide and phytohormone interactions: current status and perspectives - Freschi, Luciano (Frontiers in Plant Science, 2013)
Nitric oxide (NO) is currently considered a ubiquitous signal in plant systems, playing significant roles in a wide range of plant responses to environmental and endogenous cues. During the signaling events leading to these plant responses, NO frequently interacts with plant hormones and other endogenous molecules, at times originating remarkably complex signaling cascades. Accumulating evidence indicates that virtually all major classes of plant hormones may influence, at least to some degree, the endogenous levels of NO. In addition, studies conducted during the induction of diverse plant responses have demonstrated that NO may also affect biosynthesis, catabolism/conjugation, transport, perception and/or transduction of different phytohormones, such as auxins, gibberellins, cytokinins, abscisic acid, ethylene, salicylic acid, jasmonates and brassinosteroids. Although still not completely elucidated, the mechanisms underlying the interaction between NO and plant hormones have recently been investigated in a number of species and plant responses. This review specifically focuses on the current knowledge of the mechanisms implicated in NO-phytohormone interactions during the regulation of developmental and metabolic plant events. The modifications triggered by NO on the transcription of genes encoding biosynthetic/degradative enzymes as well as proteins involved in the transport and signal transduction of distinct plant hormones will be contextualized during the control of developmental, metabolic and defense responses in plants. Moreover, the direct post-translational modification of phytohormone biosynthetic enzymes and receptors through S-nitrosylation will also be discussed as a key mechanism for regulating plant physiological responses. Finally, some future perspectives toward a more complete understanding of NO-phytohormone interactions will also be presented and discussed.